2001
DOI: 10.1200/jco.2001.19.18.3874
|View full text |Cite
|
Sign up to set email alerts
|

Primary Gastrointestinal Non-Hodgkin’s Lymphoma: II. Combined Surgical and Conservative or Conservative Management Only in Localized Gastric Lymphoma—Results of the Prospective German Multicenter Study GIT NHL 01/92

Abstract: Although the study was not randomized, a stomach-conserving approach may be favored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
117
4
16

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 217 publications
(141 citation statements)
references
References 29 publications
4
117
4
16
Order By: Relevance
“…20,21 The benefit of radiotherapy might be its curative potential for attacking low-grade lymphoma components because the presence of low-grade lymphoma components can contribute to local relapse. 22 Unlike gastric DLBCL, the association of lowgrade lymphoma components with the risk of relapse is still controversial in primary intestinal DLBCL; the presence of lowgrade components is not consistent among previous studies of intestinal DLBCL. 3,19,23 The intestine is less suitable for radiotherapy than is the stomach.…”
Section: Discussionmentioning
confidence: 70%
“…20,21 The benefit of radiotherapy might be its curative potential for attacking low-grade lymphoma components because the presence of low-grade lymphoma components can contribute to local relapse. 22 Unlike gastric DLBCL, the association of lowgrade lymphoma components with the risk of relapse is still controversial in primary intestinal DLBCL; the presence of lowgrade components is not consistent among previous studies of intestinal DLBCL. 3,19,23 The intestine is less suitable for radiotherapy than is the stomach.…”
Section: Discussionmentioning
confidence: 70%
“…[13][14][15][16][17][18]30,31,45,46 Although past studies showed that surgical resectability was of significance, recent studies have demonstrated that nonsurgical strategies and surgery-based modalities had an equivalent efficacy. 30,31,45 Based on all these observations, and taking patients' quality of life into consideration, nonsurgical treatment is an alternative and optimal therapeutic modality for gastrointestinal lymphoma. Further randomized prospective studies with a large number of patients are still needed to establish …”
Section: Discussionmentioning
confidence: 99%
“…Surgery has been abandoned in recent years. 12,13 Radiation therapy has been used either as sole treatment or as an adjunct to surgery and had produced good control of the disease in patients who have localized lymphoma. 14,15 Several prospective studies have produced encouraging results with chemotherapy, such as cyclophosphamide, chlorambucil, 2-chorodeoxyadenosine (2CdA), and combinations with fludarabine or other drugs.…”
mentioning
confidence: 99%